MOOCs a Renaissance in Indian School Education: Review in Context of SARS-CoV-2 and NEP2020 - Hooda, Madhuri (Voices of Teachers and Teacher Educators, 2023)
The education systems of all the countries of the world have faced unprecedented challenges due to Covid-19. India also sailed the same boat along with some of its inherent challenges of its education system like; poor access, disparity in access to different socio-economic sections of society, poor quality, based on information transaction, poor skill development, fragmented system and many more. In response to this,Indian schools had swiftly adopted emergency remote teaching. When Indian school system was being badly shaken with these turbulences, it had a ray of hope to combat all these challenges and the country came out with NEP 2020. Implementation of NEP 2020 and Covid-19 effects are going simultaneously. NEP 2020 is envisioning online education and MOOCs as panacea for most of these challenges and Covid-19 is also pushing Indian school education system for a shift to online mode of education. MOOCs are novel educational phenomena gaining momentum and popularity worldwide due to its potential to address the issues of access, equity and quality. The article has critically discussed the impact of Covid-19 over Indian school education, along with the aspiration of NEP to radically transform the whole Indian education system. Various digital initiatives (ATLs, NEAT, DIKSHA, ePGPathshala, etc.) by MoE have been discussed. Article has also thrown light on NEP’s vision of leveraging ICT in teaching and learning; and developing MOOCs as a new techno pedagogical innovation. The article also attempts to explore the real potential of MOOCs in addressing the issues of school education along with some inherent challenges